A Fatal Case Report of Barium Chloride Toxicity. Issue 2 (14th December 2022) - Copeland, Caroline S; Rock, Kirsten L; Pinhal, Andreia; Chapman, Robert C; Chilcott, Robert P
Abstract: Barium is an alkaline earth metal whose toxicity is dictated by its compounded salt form: barium sulfate is insoluble and safe to ingest, but other barium salts (chloride, carbonate, sulfide, oxide and acetate) are bioavailable and therefore toxic when ingested. There have been 49 previous reports of fatal intoxications following barium consumption: 38 deemed accidental in nature, 8 suicidal, 1 homicidal and 2 of undetermined intent. In this report, we detail the first intentional fatal self-poisoning with barium chloride to be reported in the UK, along with a review of the surrounding literature. This is the first case to report quantified levels of barium in blood and vitreous humor, and by providing details of sample collection, storage and processing, this case will aid in future interpretations.